The Role of Environmental, Social, and Governance Aspects in Achieving Sustainable Development Goals - Hariyono, Cherish Sheverine; Wijaya, Grace Antoneta; Widianingsih, Luky Patricia (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2025)
Many efforts have examined the determinants that influence the extent to which countries fulfill their sustainability goal commitments. This study explores how Environmental, Social, and Governance (ESG) factors influence the achievement of Sustainable Development Goals (SDGs) across 160 countries. The data were analyzed using multiple linear regression. ESG and Gross Domestic Product (GDP) growth data were obtained from the World Bank, while the SDG Index data were sourced from the Sustainable Development Report publication. The results show that ESG has a significant positive effect on the SDG Index, while GDP growth exhibits only a weak effect. These findings emphasize the need for countries to promote more sustainable and responsible business practices, as ESG can help create a conducive environment for achieving the SDGs. Meanwhile, GDP growth alone will have limited value if it is not sustainable. Economic growth targets and sustainability goals need to be integrated so they reinforce one another. Therefore, countries should focus not only on the growth rate but also on per capita achievements that have a direct impact on citizens’ well-being.